Acute Respiratory Failure due to Neuromyelitis Optica Treated Successfully with Plasmapheresis - Massa Zantah; Timothy B. Coyle; Debapriya Datta (Case Reports in Pulmonology)
Neuromyelitis Optica (NMO) is a demyelinating autoimmune disease involving the central nervous system. Acute respiratory failure from cervical myelitis due to NMO is known to occur but is uncommon in monophasic disease and is treated with high dose steroids. We report a case of a patient with NMO who developed acute respiratory failure related to cervical spinal cord involvement, refractory to pulse dose steroid therapy, which resolved with plasmapheresis.